Integrasi Keilmuan Program Studi Tadris (Umum) Fakultas Tarbiyah dan Keguruan IAIN Raden Intan Lampung - Murtadho, Ali (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Science (science) and religion (religion) in practice often have a different paradigm. Science (Science) in seeking and finding the truth generally dotted beneath the rationalism-empiricism. Science paradigm is generally considered to have a neutral nature of ethics and ideology-neutral, so it is objective. While the paradigm used religion (religion) in seeking and finding the truth is usually based on dogma, rites, and myths. In the spirit of transcendental religion (divine revelation) which is absolute. Therefore, the truth of religion can not be denied. This is what makes the two camps often do not greet each other, eventually gave birth to the attitude of negating one another. Reality is indeed pointed out, the existing education system in Indonesia there are two kinds: general education and education (to) religion (an). In practice both the education system, as being in "a different world". Walk on their own and then bring up the notion that if "religion" and "science" are two different entities and difficult to reconcile. This paper attempts to center an integration of science that has been pursued by the Faculty of MT & Teaching IAIN Raden Intan Lampung. In addition, this paper is based on field research. This study aims to determine the structure of curriculum department of public (Tadris) Faculty of MT IAIN Raden Intan Lampung, would have described the spirit of integration of science and to investigate the integration effort of knowledge in the learning process, in addition to determine the factors that become obstacles in the effort to develop the integration of science Reviewed Tadris department of Faculty of MT IAIN Raden Intan Lampung.